2021
DOI: 10.3389/fonc.2021.709070
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Evaluation of the Accuracy of Various Lymph Node Staging Criteria in Rectal Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundMagnetic resonance imaging (MRI)-based lymph node staging remains a significant challenge in the treatment of rectal cancer. Pretreatment evaluation of lymph node metastasis guides the formulation of treatment plans. This systematic review aimed to evaluate the diagnostic performance of MRI in lymph node staging using various morphological criteria.MethodsA systematic search of the EMBASE, Medline, and Cochrane databases was performed. Original articles published between 2000 and January 2021 that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…[16] However, MRI is less accurate for N staging than T staging, with sensitivity and specificity values ranging between 58% and 77% and 62% and 74%, respectively. [17][18][19] Multivariate logistic regression analysis revealed that the LN size and T stage were independent predictors of preoperative LN metastasis. Lim et al [20] showed that LN metastasis in rectal cancer is associated with the maximum short diameter of the LNs.…”
Section: Discussionmentioning
confidence: 99%
“…[16] However, MRI is less accurate for N staging than T staging, with sensitivity and specificity values ranging between 58% and 77% and 62% and 74%, respectively. [17][18][19] Multivariate logistic regression analysis revealed that the LN size and T stage were independent predictors of preoperative LN metastasis. Lim et al [20] showed that LN metastasis in rectal cancer is associated with the maximum short diameter of the LNs.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the eight patients studied had an initial N + tumor according to routine EUS and MRI. The initial lymph node involvement, especially the lymph node response after CT and RCT, is difficult to specify formally[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In daily practice, radiologists define lymphadenopathy in the upper abdomen primarily on size criteria, a short axis of > 10 mm. However, there are various reports that the size-criterion is not specific enough for various cancers 19 20 . Cross-sectional imaging could potentially assist in locating LNs to facilitate a more targeted approach for EUS-TA.…”
Section: Discussionmentioning
confidence: 99%